Anaphylaxis to IGIV in immunoglobulin-naïve common variable immunodeficiency patient in the absence of IgG anti-IgA antibodies: successful administration of low IgA-containing immunoglobulin. Issue 1 (December 2016) - Gharib, Asal; Caperton, Caroline; Gupta, Sudhir
Abstract Although severe reactions to immunoglobulin preparations have been frequently reported, IgE antibodies against IgA are usually not investigated; and occur predominantly in previously sensitized patients. The purpose is to report anaphylaxis to IGIV during initial infusion in a patient with common variable immunodeficiency with absent IgA without prior sensitization and in the absence of detectable IgG anti-IgA antibodies, and positive skin tests for immediate hypersensitivity to four different preparations of IGIV, one subcutaneous immunoglobulin preparation, and to purified IgA. Patient was treated without side effects with IGIV preparation depleted of IgA to which immediate hypersensitivity skin test was negative. This case demonstrates that patients with CVID with no IgA and without prior exposure to immunoglobulin or plasma may develop anaphylaxis following initial infusion of IGIV, which appears to be due to IgE anti-IgA, and independent of IgG anti-IgA antibodies. Since there is no good correlation between anaphylaxis/anaphylactic reactions and IgG anti-IgA antibodies, and IgE anti-IgA antibody test is commercially unavailable, we suggest that the patients with CVID with absence of IgA might be skin tested for immediate hypersensitivity prior to initiation of immunoglobulin administration. However, such recommendation may require studies on a large number of patients with CVID with no detectable IgA.